USULAN PENJADWALAN KEDATANGAN TRUK DI DEPO PETI KEMAS X DENGAN PENDEKATAN OPTIMISASI BERBASIS SIMULASI - Rubens, Rafael
The total number of goods that must be unloaded and loaded in Indonesia in 2023 has increased so that the quality of the maritime logistics and transportation system must also be considered, including PT Kawasan Berikat Nusantara (KBN) Cakung. However, the Container Depot X is experiencing problems due to increase in Truck Round Time (TRT) which exceeded the set standards. This research is aimed at overcoming this problem by scheduling trucks to increase depot efficiency and minimize the average TRT.